2023
DOI: 10.32602/jafas.2023.002
|View full text |Cite
|
Sign up to set email alerts
|

Expectations Gap, Market Skills, and Challenges of Accounting Education in Saudi Arabia

Abstract: Purpose: This study investigates accounting graduates' skills gap and the required market skills from the perception of accounting faculty and professionals in accounting firms in Saudi Arabia. It also explores the challenges accounting programmes and faculty face in due rapid changes. Methodology: The research uses a combination of methods and data sources. Findings: The findings show a gap between accounting education and the labour market demands. Accounting programs focus on technical skills and less on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A good level of technical knowledge alone may set the context for developing competences such as critical thinking, communication, ethics, etc. [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A good level of technical knowledge alone may set the context for developing competences such as critical thinking, communication, ethics, etc. [7,8].…”
mentioning
confidence: 99%
“…Based on Arquero's study [8], Howcroft [12] showed that educators, professional bodies and employers have divergent points of view concerning master's students' competences. Educators think employers are more interested in graduates' technical competences than in their critical thinking skills and other vocational competences.…”
mentioning
confidence: 99%